Research on the multiuser MIMO linear cooperative spectrum sensing in cognitive radio networks - Yong-qiang HEI; Xiao-hui LI; Wen-tao LI (Tongxin xuebao)
The multiuser MIMO based linear cooperative spectrum sensing problem was investigated in cognitive radio system to improve the reliability of spectrum sensing.Both the local spectrum detecting strategy and global spectrum detecting strategy for multiuser MIMO based linear cooperative spectrum sensing system were derived.Then the optimization model that the different weights assigned on the receive signals of each user at the fusion center for global decision were optimized to maximize the detection probability given a targeted probability of false alarm is established.Furthermore,genetic algorithm (GA) was introduced to find the optimal weight vector of the above-mentioned cooperative spectrum sensing problem,with the purpose of reducing the sensing time in the spectrum sensing process.The simulation results show that,the reliability of spectrum sensing in cooperative spectrum sensing system can be efficiently enhanced with multiple antennas.Besides,the proposed GA method is efficient and stable,and achieves better detection performance when compared with the existing methods.